Management of Gartland Type 1 Supracondylar Fractures: A Systematic Review - Stephanie Coupal; Kenneth Lukas; Amy Plint; Maala Bhatt; Kevin Cheung; Kevin Smit; Sasha Carsen (Frontiers Media S.A., 2022)
PurposeGartland Type 1 supracondylar humerus fractures are stable, non-displaced injuries treated with non-operative management. This systematic review was performed to gather evidence on the optimal form of immobilization to treat these fractures.MethodsThe review process was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. An electronic search was performed in November 2020. Articles were eligible if they included children less than 18 years old, with non-displaced supracondylar fractures, treated non-operatively. Randomized trials, quasi-experimental trials, and prospective cohort studies were included. Outcomes of interest included fracture displacement, pain control, time to return to normal activities, return of range of motion (ROM), child/parent satisfaction, adverse events, and cost. Risk of bias was assessed using the Newcastle-Ottawa scale, Rob-2, and the ROBINS tools.ResultsAfter duplicate records were removed, 525 records were evaluated with 9 studies meeting the inclusion criteria and 5 reporting clinical outcomes. The studies were heterogenous, in intervention and outcomes, and all at moderate risk of bias. Within the available evidence there were no cases of fracture displacement. Two small studies suggested that cuff and collar treatment provided inadequate pain control and delay in return to normal activities, compared to posterior splints. Two randomized control trials (RCTs) suggested that soft fiberglass casts reduced appointment time and increased parent satisfaction, compared to traditional casts. No studies directly compared posterior splints to circumferential casts.ConclusionThere is insufficient high-quality evidence to determine the optimal conservative treatment for patients with Gartland type 1 supracondylar fractures. Level of Evidence Level II systematic review of Level II studies.Systematic Review Registration[PROSPERO], identifier [CRD42020144616].